LAJU PERTUMBUHAN DAN PERAMETER LINGKUNGAN BUDIDAYA RUMPUT LAUT Eucheuma cottonii METODE RAKIT APUNG DI PULAU SEMUJUR, BANGKA TENGAH - La Ode Wahidin; Rudiansyah; Rully Bintan Samudra; Muhammad Royansyah (Journal of Aquatropica Asia, 2026)
This study aimed to analyze the growth rate of Eucheuma cottonii and evaluate environmental parameters in a floating raft cultivation system at Semujur Island, Central Bangka. The study was conducted from September to November 2025 using seedlings obtained from South Lampung. Observed parameters included biomass growth, specific growth rate (SGR), temperature, salinity, dissolved oxygen, current velocity, and tidal conditions. The results showed that the floating raft method provided good growth performance. During the first 30-day cultivation period, biomass increased from 1,400 g to 2,500 g with a daily SGR of 1.93%. In the following 30-day period, biomass increased to 6,500 g, representing a 160% increase with a daily SGR of 3.19%. The improved growth in the second phase indicated seed adaptation to local environmental conditions. Water quality parameters during the study were within suitable ranges for seaweed growth, with temperature of 29–33°C, salinity of 31–32 ppt, dissolved oxygen of 6.0–6.8 mg/L, and current velocity of 0.21–0.27 m/s. Based on the findings, Semujur Island has a strong potential for cultivating the species respecting to the local environmental condition.